Ciclo vital y morfología larval de Euglyphis rivulosa (Lepidoptera: Lasiocampidae) en laboratorio - Fischer, Heitor Z (1994)
The lepidopteran Euglyphis rivulosa, an important pest in avocado plantations. was Itudied under laboratory cooditioos. The eggs were cylindrical, black and averaged 1.01 ± 0.05 mm in length and 0.82 ± 0.03 mm in width. The mean incubation periad was 6.46 ± 0.82 days. The larval stage averaged 36.14 ± 1.06 days, presenting sn larval instara. 'The duration oí pre-pupal and pupal stages were 2.00 ± 0.63 and 9.93 ± 1.90 days, respectively. Adult longevities did not düfer between the sexes. Females did not presenl preference for oviposition sites and egg masses varied in form and number of eggs. There were 203.72 ± 111.96 eggs per female. The females utilize 52% oC their reproductive capacity during the firsl three days of their lüe span with 100% survivorship. 'The reproductive capacity of!he femalea in relation 10 their age is represented by the formula Y=42.88-3.63 x.